Electroconvulsive therapy efficacy in adolescents with mental illness: A retrospective comparison - Si, Qi; Zhang, Xinyue; Lei, Jiaxi; Chen, Congxin; Ren, Fangfang; Xu, Guoxin; Li, Yuan; Sui, Yuxiu (Frontiers in Psychiatry, 2022)
Background There is limited evidence on the efficacy of electroconvulsive therapy (ECT) in adolescents with mental illness. The present study reported outcomes of adolescents with mental illness treated with ECT aimed at providing evidence for large-scale feasibility. Objectives The primary objective of this trial was to examine the differences in demographic and clinical data between responders and non-responders. The secondary objective was to determine whether ECT produced differential readmission rates, the burden of oral medication, and social function in responders and non-responders in the long term. Methods Patients aged 14~18 years diagnosed with schizophrenia (SCZ), major depressive disorder (MDD), or bipolar disorder (BD) who received ECT between 2015 and 2020 were included in the study. Demographic and clinical data were compared, and both short-term and long-term outcomes were assessed: response on the Clinical Global Impressions-Improvement scale and readmission at follow-up. The independent-sample t test was used to compare the continuous variables and the X2 test was used to compare the dichotomous variables with statistical significance at P≤0.05. Results 410 adolescents (aged 14~18 years, 53.90% female) received ECT for SCZ, MDD, and BD. The response rate for SCZ, MDD, and BD were 65.61%, 78.57%, and 69.95%, respectively. Both SCZ (P = 0.008) and BD (P = 0.008) groups had a significant elder age in responders than in non-responders. Besides that MDD responders had a significantly larger number of ECT sessions than non-responders (P = 0.046), the study failed to find a significant difference in other ECT parameters. A significantly higher proportion of readmission was found in BD non-responders than in responders (P = 0.029), there was no difference in the rate of readmission in other diagnostic groups. Conclusions These data suggested that ECT is an effective treatment for adolescents with severe mental illness, and the rate of readmission was low in the long term. The present study supports that large-scale systematic studies are warranted for further investigation of the response rate of ECT for treating adolescents with mental illness.